Reliability modeling and analysis of uncertain competing failure systems - Gao, Rong; Li, Xinyang (Computers & industrial engineering, 2024)
The competing failure system is quite common in real life, such as automotive system and aerospace system. Two distinct failure modes usually coexist in this type of system: gradual internal degradation and sudden external shock, where the occurrence of any failure mode can lead to the system failure. The system failure such as aircraft accident may cause a terrible loss of human life and property. Hence, it is worth reducing the rate of system failure by improving the system reliability. While, reliability model is the foundation of any research of reliability and epistemic uncertainty exists in the process of modeling and estimating. Therefore, we introduce uncertainty theory to investigate the competing failure system with epistemic uncertainty. The internal degradation and external shock of the system are characterized by an uncertain differential equation and an uncertain renewal process, respectively. The system reliability is defined as the uncertain measure that neither internal degradation nor external shock surpass corresponding thresholds. In addition, some reliability formulas are derived for the systems subjected to extreme shock, cumulative shock, running shock and δ-shock, respectively. Finally, a case study with respect to micro-electro-mechanical system is given to show how the proposed model is implemented. •We use uncertainty theory to investigate the competing failure system with epistemic uncertainty.•The system reliability is obtained by employing uncertainty theory.•The internal degradation of the system is characterized by an uncertain differential equation.•The external shock of the system is characterized by an uncertain reward process.•Some reliability formulas are derived for four types of external shock.